The Role of Law Enforcement in Managing Communal Conflict - Sisinaru, Sostones Yakobis; Basuki, Eko; Maspaitella, Marthin Jonas (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Research on communal conflict in Maluku has received little attention from researchers in the fields of law and social sciences.Purposes of the Research: This study was conducted to understand communal conflict in Maluku and the role of the police in managing it.Methods of the Research: This study used a qualitative approach, with narrative analysis used for data analysis.Results of the Research: Village boundary disputes and interpersonal conflicts remain the dominant factors influencing the emergence of communal conflict within society. Law enforcement agencies, particularly the police, are considered not yet optimal in implementing anticipatory and preventive measures to address the potential escalation of communal conflict. Furthermore, the police intelligence function is viewed as not fully effective in conducting early detection of social frictions and emerging conflict potentials within the community. Communal conflicts have the potential to generate prolonged collective resentment, thereby increasing societal vulnerability to provocation and involvement in communal violence against individuals or groups with whom they have previously been in conflict. In the context of handling customary territorial boundary disputes between the Sawai and Huaulu communities, the police, in collaboration with judicial institutions, have undertaken legal resolution efforts in accordance with applicable procedures and statutory regulations. Nevertheless, segments of the community who perceive themselves as disadvantaged by the legal decisions have not been able to fully accept the outcomes of those rulings. Therefore, the police and other law enforcement institutions need to intensify legal outreach and public legal awareness education, particularly among conflict-prone indigenous communities, regarding disputes over territorial boundaries or customary land.